2022
DOI: 10.1101/2022.09.21.22280179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut inflammation associated with age and Alzheimer’s disease pathology

Abstract: Age-related disease may be mediated by low levels of chronic inflammation ("inflammaging"). Recent work suggests that gut microbes may contribute to inflammation via degradation of the intestinal barrier. While aging and age-related diseases including Alzheimer's disease (AD) are linked to altered microbiome composition and higher levels of gut microbial components in systemic circulation, the role of intestinal inflammation and permeability per se remains unclear. To test whether greater gut inflammation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Conversely, AD patients showed an increase in Ruminococcus species, which was associated with lower levels of N-acetylaspartate, which is an indicator of neuronal health (Zhuang et al, 2018). This dysbiosis links to neuroinflammatory processes (Sochocka et al, 2019) particularly microglial activation (Cerovic et al, 2019), and compromises intestinal barriers (Honarpisheh et al, 2020;Heston et al, 2023). This allows inflammatory substances into circulation, contributing to brain inflammation.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Conversely, AD patients showed an increase in Ruminococcus species, which was associated with lower levels of N-acetylaspartate, which is an indicator of neuronal health (Zhuang et al, 2018). This dysbiosis links to neuroinflammatory processes (Sochocka et al, 2019) particularly microglial activation (Cerovic et al, 2019), and compromises intestinal barriers (Honarpisheh et al, 2020;Heston et al, 2023). This allows inflammatory substances into circulation, contributing to brain inflammation.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Gut inflammation has been associated with AD/ADRD risk [29], suggesting that the gut microbiome may contribute to 'inflammaging' in AD/ADRD. Prior studies focusing on microbiome and AD/ADRD have reported reduction in diversity [30], and lower abundance of beneficial anti-inflammatory taxa, such as Eubacterium spp.…”
Section: Introductionmentioning
confidence: 99%